AN EVALUATION OF ANTIOXIDANT, ANTIMICROBIAL, ANTIBIOFILM AND CYTOTOXIC ACTIVITIES OF FIVE VERBASCUM SPECIES IN TURKEY - TAŞKIN, TURGUT (#N/A, 2018)
Verbascum L. species are used for different medicinal purposes in Turkish folk medicine such as diuretic, expectorant, laxative, mucolytic, sedative, sudorific, and wound healer. Five Verbascum species, two of which are used in medicine, were investigated for their antimicrobial, antioxidant and cytotoxic activities. Determination of the total phenolic compounds, DPPH and ABTS methods were preferred for the antioxidant tests. The antimicrobial and antibiofilm activities of the extracts, which were not studied previously, were investigated against pathogenic and potential pathogenic agents. The cytotoxicity was assessed by MTT and LDH tests. This study is very important for finding new therapeutic sources and also new, natural sources for food preservation.
Keywords: Verbascum species; antioxidant; antimicrobial; antibiofilm; cytotoxicity; food preservation